The Ottoman Crimean War (1853-1856) - Badem, Candan (Brill, 2010)
This book analyzes the Crimean War from the Ottoman perspective based mainly on Ottoman and Russian primary sources, and includes an assessment of the War’s impact on the Ottoman state and Ottoman society.